Comparing the Effect of 8 Weeks of Total Body Resistance Exercise and Core Stability Training on Selected Common Abnormalities and Postural Control in Deaf Adolescents - Foroogh Zakeri; Farzaneh Taghian (Shiraz University of Medical Sciences, 2020)
Background: Deafness is the most common sensory-neurological defect in human beings. This study aimed to compare the effect of 8 weeks of Total Body Resistance )TRX( and core stability training on balance and some common abnormalities among deaf adolescents. Methods: This study was conducted with a two-group pretest-posttest quasi-experimental study design. The participants included in this study were 20 hearing-impaired students with a degree of deafness between 71-90 dB in Bandar Abbas city who were purposefully selected and then randomly assigned into two groups, as TRX (N=10) and core stability training (N=10). In this study, static balance, dynamic balance, kyphosis and lumbar lordosis, and forward head were measured before and after eight weeks in both groups using one-leg stance test, Y balance test, flexible ruler, and goniometer, respectively. The core stability training consisted of 10 different exercises in the core in terms of the progressing and the TRX protocols. Moreover, these exercises were performed 3 sessions per week for an 8-week period (1 day in between), and each session lasted for 40 minutes. The dependent and independent t-tests were also used to perform the intra-group and inter-group comparisons, respectively. The statistical significance level was set at p ≤ 0.05. Results: The research results show that the abnormalities in the two methods of static balance with open and closed eyes as well as dynamic balance were equally evaluated based on the independent t-test and there was no significant difference between these two methods (p ≥ 0.05). Also, in the forward head, kyphosis, and lordosis variables, the performances of these two methods to reduce the abnormalities were equally evaluated. In this regard, no significant difference was observed between the performances of these two methods (p ≥ 0.05). However, there was a significant difference between the effects of TRX exercises and core stability training on dynamic balance (p ≤ 0.05). Conclusion: Therefore, to reduce abnormalities and improve balance in deaf children, both methods can be considered as effective with no difference.